Penanaman Moral Anak Melalui Kisah-Kisah Teladan Dalam Pembelajaran Akhlak Pada Siswa Kelas IV SD Muhammadiyah 14 Surakarta Tahun 2016/2017 - Prasetyo, Imam Heri; , Dra. Sri Hartini, S.H., M.Pd (2017)
This study aims to describe : 1) Understanding of teachers about moral education in fourth grade students of SD Muhammadiyah 14 Surakarta, 2) Implementation of moral cultivation of children through exemplary stories in moral learning, 3) Moral values implanted in fourth grade students SD Muhammadiyah 14 Surakarta, 4) Inhibiting factors or obstacles experienced by teachers in the implementation of moral cultivation of fourth graders of SD Muhammadiyah 14 Surakarta, 5) Efforts in overcoming barriers in moral cultivation of fourth grade students of SD Muhammadiyah 14 Surakarta. The type of research is qualitative and research design is case study. Data collection techniques such as interviews, observation, and documentation. Data validity uses triangulation with multiple sources and triangulation with many techniques. Data analysis techniques in this study include: data reduction, data presentation, and conclusion. The result of the research shows that 1) the teacher already understand about the nature of moral education and the purpose of moral planting well, 2) moral cultivation in moral learning taken from the manual of Al-Islam and Kemuhammadiyahan book and the story of the Companions of the Prophet SAW, 3) The moral values that are instilled, among others, repentance, the nature of patience, diligent study, sincere charity, patience and patience, respect to people, courage, berqurban, humble, helpful, obedient worship, honesty, trust, simple life, peace / peace , Pema'af, grateful, cooperative, and discipline, 4) Inhibiting factors or obstacles experienced by teachers in the implementation of child moral planting through exemplary stories, among others: the lack of self-awareness of students of the importance of moral values for himself, poor supervision from family / parents, and the influence of social environment (5) Efforts to overcome obstacles in child moral cultivation through exemplary stories, among others, students are asked to practice or present forward in the material of exemplary stories. Teachers often do intermezzo, ice breaking, or distraction, establish cooperative relationships between educators with parents and teachers impose penalties and rewards to students.